In the search for the perfect prompt in medical AI queries - Berghea, Florian; Berghea, Elena Camelia; Daia, Cristina Octaviana; Ciuc, Diana; Dinca, Gabi Valeriu (Frontiers in Artificial Intelligence, 2025)
The evaluation of medical Artificial Intelligence (AI) systems presents significant challenges, with performance often varying drastically across studies. This narrative review identifies prompt quality—the way questions are formulated for the AI—as a critical yet under-recognized variable influencing these outcomes. The analysis explores scientific literature published between January 2018 and August 2025 to investigate the impact of prompt engineering on the perceived accuracy and reliability of conversational AI in medicine. Results reveal a “performance paradox,” where AI sometimes surpasses human experts in controlled settings yet underperforms in broader meta-analyses. This inconsistency is strongly linked to the type of prompt used. Critical concerns are highlighted, such as “prompting bias,” which may invalidate study conclusions, and AI “hallucinations” that generate dangerously incorrect information. Furthermore, a significant gap exists between the optimal prompts formulated by experts and the natural queries of the general public, raising issues of safety and health equity. In the end we were interested in finding out what the optimal balance existed between the complexity of a prompt and the value of the generated response, and, in this context, whether we could attempt to define a path toward identifying the best possible prompt.